RELIABILITY СONTROL OF ELECTRIC NETWORK SYSTEM AT JOINT-STOCK COMPANY «LENENERGO» UNDER CONDITIONS OF POWER ENGINEERING MODERNIZATION - A. P. Vasiliev; A. G. Tourlov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
During the last decade a general trend is observed among power engineering companies towards the deregulation of production activity. This social and political movement causes revaluation of reliability control of electric network system policy at Joint-Stock Company «Lenenergo», elaboration and development of methods and means for solution of integrated problems involving the whole process from putting into operation till equipment writing off.